2021
DOI: 10.1002/hep4.1866
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ‐induced FOXS1 controls epithelial–mesenchymal transition and predicts a poor prognosis in liver cancer

Abstract: Transforming growth factor beta (TGF‐β) plays a key role in tumor progression, notably as a potent inducer of epithelial–mesenchymal transition (EMT). However, all of the molecular effectors driving TGFβ‐induced EMT are not fully characterized. Here, we report that forkhead box S1 (FOXS1) is a SMAD (mothers against decapentaplegic)–dependent TGFβ‐induced transcription factor, which regulates the expression of genes required for the initial steps of EMT (e.g., snail family transcription repressor 1) and to main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…Like alpha-fetoprotein (AFP) in HCC, FOXS1 may have the oncofetal expression pattern: a peculiar gene highly expressed in embryonic tissues and silenced in normal adult cells but reactivated in tumors. 31 , 32 This view has been confirmed in our study as the FOXS1 promoter methylation level was negatively correlated with its transcription in most cancer types. A high FOXS1 promoter methylation level can serve as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 84%
“…Like alpha-fetoprotein (AFP) in HCC, FOXS1 may have the oncofetal expression pattern: a peculiar gene highly expressed in embryonic tissues and silenced in normal adult cells but reactivated in tumors. 31 , 32 This view has been confirmed in our study as the FOXS1 promoter methylation level was negatively correlated with its transcription in most cancer types. A high FOXS1 promoter methylation level can serve as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 84%
“…The role of FOXS1 in the development and progression of human cancers is largely unknown. There are only a few studies that have reported that FOXS1 was involved in the regulation of cancer cell biology in gastric cancer ( 24 , 25 ), hepatocellular carcinoma ( 26 , 27 ), and glioma cells ( 28 ). Nevertheless, the role of FOXS1 in cancer remains controversial according to the results from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A high expression of FOXS1 predicted a poor prognosis in liver cancer. In addition, overexpression of FOXS1 induced EMT markers and promoted cell migration and metastasis in liver cancer ( 26 ). On the contrary, Lei et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations